Prosthetic Valve Endocarditis: A Complication of Spinal Epidural Abscess - Armando Bedoya; Bethany Gentilesco (Case Reports in Medicine)
Epidural injections for chronic low back pain are controversial, and their effectiveness is debated. Although epidural injections are considered a minor procedure with low morbidity, catastrophic complications may occur. We describe a case of prosthetic valve endocarditis secondary to an epidural abscess after epidural injection to alert clinicians to this unusual association.